Hypersensitivity due to Chlorhexidine Digluconate Mouthwash: A Report of an Uncommon Case - Bhandari, Suresh; Shrestha, Sajeev; Adhikari, Khushbu; Acharya, Pujan; Thapa, Victory (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Chlorhexidine is a commonly used mouthwash in dentistry with proven benefits for various periodontal conditions. Various minor side effects may occur after its use in the oral cavity. However, in some uncommon cases, more severe signs and symptoms may develop, which require prompt attention. The present case report describes the clinical findings and management in one such instance where a patient developed a delayed hypersensitivity reaction a few days after the use of Chlorhexidine digluonate mouthwash. The signs and symptoms of the patient gradually subsided after the discontinuation of the mouthwash and the use of an oral antihistaminic medication.